Plasma Constituents in the Sow: Minerals, Glucose, Urea-N, Protein and Transaminases in Relation to Weaning - Benjaminsen, Eduard (Acta Vet Scand, 2021)
The concentrations in plasma of total protein, urea-N, Ca, Mg, Na and K and the activity of aspartate aminotransferase (ASAT) and alanine aminotransferase (ALAT) in plasma were studied in 20 sows from one week before weaning until four weeks after weaning. Ten of the sows resumed ovarian activity within 10 days after weaning, while in the other 10 sows the resumption of ovarian activity was delayed. Plasma glucose was studied in 10 sows from one week before weaning until two weeks after weaning, five of these sows had delayed resumption of ovarian function. After weaning the concentration of total protein and the ALAT activity increased, while plasma glucose and Mg decreased. Concerning ASAT, Ca, Na and K no changes were observed. A transient increase in urea-N level took place after weaning in sows with prolonged weaning-to-ovulation period. In sows with normal weaning-to-ovulation period no change in urea-N was observed. This was the only difference in blood chemistry observed between sows with normal weaning-to-ovulation period and sows with prolonged weaning-to-ovulation period.